(In)Formal memoryscapes and the unma(s)king of a Malaysian war heroine. Issue 3 (November 2014) - Muzaini, Hamzah
<x xml:space="preserve">Abstract</x> The geographical literature on the politics tied to formal commemorations of the past is a burgeoning one. Yet, there has been less attention paid to similar practices undertaken by nonstate agents seeking to ensure that what is written out of official history is not forgotten. This paper explores how and why the story of Sybil Kathigasu, a woman who played a salient role in the resistance movement against the Japanese during the Second World War in Perak, Malaysia, has been peripheralized within formal memory making even as it has been informally revived elsewhere. It specifically suggests that, while the sidelining of her story may be the product of the tendency of the state of Perak to downplay its war past, Sybil's gender, race and political ideologies have also made it more difficult for her to be embraced as a 'national' heroine. Drawing on a private museum that was set up in her honor in Papan, the paper also reveals how factors impeding her formal remembrance also have implications for alternative efforts to recover her story. More broadly, the paper offers insights into women's absences in Malaysian public memory, and argues the need for more emphasis on memoryscapes 'from below' as a means of nuancing local remembrance politics.